Structural characterization and electrochemical properties of (La, Sr)(Al, Mg)O4−δ perovskites. (26th June 2020) - Mariño, C.; Basbus, J.; Alonso, J. A.; Troncoso, L.
Abstract : LaSrAl1− x Mg x O4− δ ( x = 0.0–0.3) layered perovskites were synthesized by a nitrate–citrate route followed by annealing in air at 1100 °C, and studied as potential electrolyte materials in solid oxide fuel cells (SOFCs). Abstract : LaSrAl1− x Mg x O4− δ ( x = 0.0–0.3) layered perovskites were synthesized by a nitrate–citrate route followed by annealing in air at 1100 °C, and studied as potential electrolyte materials in solid oxide fuel cells (SOFCs). The products obtained were initially characterized by X-ray diffraction (XRD). The compounds were indexed to the I 4/ mmm space group with K2 NiF4 -type structure. Neutron powder diffraction data were collected to determine the crystallographic features. A complementary study of pellets sintered at 1400 °C was performed by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS), and the segregation of secondary phases rich in Sr or La was observed for Mg contents with x ≥ 0.2. It was also noticed that Mg doping preserved the sintering capability of the compounds. Thermogravimetric (TG) measurements from green powders indicated that phase formation occurred above 900 °C. The thermal expansion coefficient (TEC) values were close to 10 × 10 −6 K −1, indicating that (La, Sr)(Al, Mg)O4− δ layered perovskites are compatible with other SOFC materials. The electrical properties for single-phase compounds ( x = 0.0 and 0.1) were studied by electrochemical impedance spectroscopy (EIS). The total conductivity at 900 °C for x = 0.1 was σ = 1.79 mS cm −1, whereas for x = 0.0, σ = 4.94 μS cm −1 . The total conductivity was three orders of magnitude higher for x = 0.1 with respect to the undoped material. The high activation energy values around 1.5 eV indicated that the transport mechanism was dominated by oxygen vacancy diffusion. The results obtained suggest that LaSrAl0.9 Mg0.1 O4− δ could be applied as an electrolyte in energy conversion electrochemical systems.